2002
DOI: 10.2337/diabetes.51.8.2561
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Human Islet Cell Functional Mass by Anti-Oxidative Action of a Novel SOD Mimic Compound

Abstract: The most commonly used technical approach to isolate human pancreatic islets intended for allotransplants generates a product that is hampered by mechanical and chemical insults, which dramatically reduce the mass of viable and functional transplantable cells. We tested a novel class of antioxidant chemical compounds (SOD mimics: AEOL10113 and AEOL10150) to protect human islets from oxidative stress in order to improve the preservation of the isolated tissue. Addition of SOD mimic in culture, after isolation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
156
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 39 publications
5
156
0
1
Order By: Relevance
“…Our further synthetic efforts in searching for a potential therapeutic based on the SAR led us to Mn(III) ortho N-alkylpyridylporphyrins as the most potent candidates for forwarding them into animal models where superoxide-mediated damage is involved. Thus remarkable effects were observed in cancer, radiation, diabetes, ALS, Alzheimer's disease etc [13][14][15][16][17][18][19][20][21][22][23]. Further, along with our mechanistic studies we observed a dramatic impact of the positive charges of the Mn porphyrin on the O 2 •− dismutation; the rate constants are more than two orders of magnitude higher when compared to the neutral or negatively charged porphyrins [3,4].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Our further synthetic efforts in searching for a potential therapeutic based on the SAR led us to Mn(III) ortho N-alkylpyridylporphyrins as the most potent candidates for forwarding them into animal models where superoxide-mediated damage is involved. Thus remarkable effects were observed in cancer, radiation, diabetes, ALS, Alzheimer's disease etc [13][14][15][16][17][18][19][20][21][22][23]. Further, along with our mechanistic studies we observed a dramatic impact of the positive charges of the Mn porphyrin on the O 2 •− dismutation; the rate constants are more than two orders of magnitude higher when compared to the neutral or negatively charged porphyrins [3,4].…”
Section: Introductionsupporting
confidence: 56%
“…In all previous studies the data obtained with E. coli parallel the trends obtained in in vivo animal model studies [1][2][3][4][5][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]37]. Here we compare the effect of Mn II Br 8 TM-3-PyP 4+ , its metal-free porphyrin HBr 8 TM-3-PyP 3+ , and the para analogue Mn II Br 8 TM-4-PyP 4+ on the aerobic growth of an SOD-deficient E. coli strain.…”
Section: Protection Of Aerobic Growth Of Sod-deficient E Colimentioning
confidence: 69%
“…Diabetes. Diabetes was studied by Piganelli et al (48,49,254,322), by using MnTE-2-PyP 5þ and MnTDE-2-ImP 5þ , and by Benov et al (44) with MnTM-2-PyP 5þ . Both MnTE-2-PyP 5þ and MnTDE-2-ImP 5þ preserved human islet cell functional mass intended for allotransplants at 34 mM.…”
mentioning
confidence: 99%
“…30,118,119 We and others have also shown that the inclusion of synthetic mimetics of free-radical scavengers seem to prevent islet degeneration possibly limiting the initiation of apoptotic processes. 105,119 Islets also take up oligonucleotides quite efficiently (unpublished observations). Knowledge of the primary transcripts whose protein products are involved in apoptosis activation or suppression of insulin production can be targeted with antisense oligonucleotides during the isolation procedure.…”
Section: Insulin Replacement Strategiesmentioning
confidence: 86%
“…There is no doubt that the time between organ retrieval and islet processing with the inherent intermediate steps including cold storage and enzymatic/ mechanical digestion affects islet yield, viability and function. 30,105 Furthermore, the culture conditions prior to transplantation can crucially affect islet cells physiology and, consequently, the chance of successful engraftment. In general, the cessation of the oxygen supply to the pancreatic tissue at the time of donor organ harvesting is known to trigger ischemic damage, free-radicalmediated cell degeneration as well as initiation of apoptosis.…”
Section: Insulin Replacement Strategiesmentioning
confidence: 99%